Adverse childhood experiences increase the risk for eating disorders among adolescents - Kovács-Tóth, Beáta; Oláh, Barnabás; Kuritárné Szabó, Ildikó; Túry, Ferenc (Frontiers in Psychology, 2022)
Purpose Traumatic events often feature prominently in eating disorders. A questionnaire survey to assess the relation of eating disorder risk to the frequency of adverse childhood experiences (ACEs) and the possible association of eating disorder risk with a particular type of ACE was conducted in a community sample of Hungarian adolescents. Methods Demographic and anthropometric data, risk for eating disorders (by SCOFF questionnaire), and ACEs (by ACE score calculator) were collected from 432 adolescents aged 12–17 years. Results Adolescents who had undergone four or more ACEs were 5.7 times more likely to be in the high eating disorder risk group than those who did not report any ACEs. Cumulative maltreatment showed a greater association with overall risk for eating disorders than cumulative family dysfunction. There is an increased risk of eating disorders from emotional maltreatment (OR = 3.475), physical maltreatment (OR = 3.440), sexual maltreatment (OR = 10.973), and emotional neglect (OR = 3.331). Dysfunctional family circumstances revealed an association with household mental illness (OR = 3.401). Conclusion Our study of the connection between eating disorder risk and ACE is the first of its kind in Central and Eastern Europe. Maltreatments had a greater role than family dysfunctions in increasing the risk of eating disorders. Our findings contribute to a more precise understanding of the role that ACEs play in eating disorders. It is important to bring to clinicians’ attention the importance of ACEs in the diagnosis and therapy of eating disorders and their potentially fundamental significance for therapy.